2019
DOI: 10.1039/c9cc04098f
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and cancer-targeting design of ruthenium complexes for precise cancer therapy

Abstract: Herein, the functionalized Ruthenium complex applied for bio-imaging, photodynamic/photothermal therapy, precise targeted therapy and theranostics application have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 136 publications
4
89
0
5
Order By: Relevance
“…with a positive charge are ideal candidates for mitochondria-targeting RSs since heavy metals with high-Z are sensitive to X-rays and positively charged materials tend to accumulate in mitochondria. 16,17 Despite the fact that using lipophilic heavy metal complexes with a positive charge as RSs can well combat the deciencies of DNA-targeting RSs, the lack of visualization of tumor sites and the low bioavailability of RSs also hinder their application. Cyclometalated iridium-based (Ir, Z ¼ 77) materials would be promising candidates for the design of novel RSs with bioimaging function due to their long-lived luminescence, good light stability and also photophysical sensitivity to acidity, oxygen content or viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…with a positive charge are ideal candidates for mitochondria-targeting RSs since heavy metals with high-Z are sensitive to X-rays and positively charged materials tend to accumulate in mitochondria. 16,17 Despite the fact that using lipophilic heavy metal complexes with a positive charge as RSs can well combat the deciencies of DNA-targeting RSs, the lack of visualization of tumor sites and the low bioavailability of RSs also hinder their application. Cyclometalated iridium-based (Ir, Z ¼ 77) materials would be promising candidates for the design of novel RSs with bioimaging function due to their long-lived luminescence, good light stability and also photophysical sensitivity to acidity, oxygen content or viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most promising alternatives to platinum-based chemotherapeutics are Ru(II) and Ru(III) complexes. They possess unique multifunctional biochemical properties and exhibit lower toxic effects than platinum-based chemotherapeutics [14,15]. In cancer cells, trivalent Ru complexes are speculated to be reduced by cellular reductants, e.g., ascorbates, to their more active divalent form.…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of Ru complexes, the cellular mode of action differs from the DNA-binding mechanism, which is typically associated with platinum-based chemotherapeutics [16]. Despite the wide range of intracellular targets, only two Ru complexes-KP1339, which is the sodium salt analogue of KP1019 (indazolium trans-[tetrachlorobis(1H-indazole)-ruthenate(III)]) and TLD1433 ([Ru(II) (4,4′-dimethyl-2,2′bipyridine)2(2-(2′,2′′:5′′,2′′′-terthiophene)-imidazo[4,5-f])]Cl2)-are currently in the clinical trials [2,[15][16][17]. While Ru(III) complexes KP1339 have been developed as chemotherapeutic agents, the octahedral Ru(II) complex TLD1433 exhibits potential for photo-dynamic therapy [16].…”
Section: Introductionmentioning
confidence: 99%
“…The development of new antitumor drugs requires understanding the mechanisms of action of new pharmacological candidates, which highlights the importance of elucidating the molecular and biochemical mechanisms involved. Recent studies have shown that some ruthenium complexes target the genomic DNA and may cause cell cycle arrest, ROS-mediated mitochondrial alterations and, finally, cell death by apoptosis 3,[7][8][9] .…”
mentioning
confidence: 99%